EVALUATION OF THE EFFECT OF ANTIOXIDANT AGENTS OF SHRIMP - SEA JELLYFISH (Catostylus sp) bioactive peptide compounds ON MACROSCOPIC CHANGES IN THE LIVER OF WISTAR RATS (Rattus novergicus) - Rayhan Putra Hasrun, Ahmad; Juniarto, M. Fajar (Jurnal Health Sains, 2024)
Jellyfish contain bioactive compounds that have the potential to act as antioxidants. Bioactive peptides in jellyfish are still rarely studied in research, so exploration regarding the benefits of bioactive compounds in jellyfish needs to be carried out. This research aims to isolate bioactive peptides from Catostylus sp. jellyfish, determine the levels of isolated protein compounds, and evaluate the antioxidant activity of bioactive peptides through in vitro and in vivo tests. The research was carried out using the method of isolating bioactive peptides through ammonium sulfate fractionation and analyzing its activity on rat as test animals. Jellyfish sample preparations were ground and extracted to obtain crude protein, which was then fractionated using ammonium sulfate. The antioxidant activity of bioactive peptides was tested using the DPPH method. Preliminary research findings indicate that bioactive peptides from jellyfish have the potential for significant antioxidant activity, with in vitro tests showing possible free radical inhibiting abilities and in vivo tests showing the potential for increased liver healing response and immune enhancement in rat.